Mechanisms of Implementing Regional Policy for Cooperation in the Sphere of Innovation Based on the Stimulation of Innovation Demand and Supply - IERMAKOVA, O. (Science and Innovation, 2022)
Introduction. The regions have a strong potential for innovation development. In the context of self-government reform, the issue of forming a regional innovation policy has become especially relevant for Ukraine, as the innovation component is a necessary prerequisite for the economic capacity of communities. Problem Statement. The world experience has shown that the innovation-driven development of regions requires the formation of regional innovation systems and relationships among all its participants. In the context of the decentralization reform in Ukraine, regional cooperation becomes one of the tools of their socio-economic and innovation-driven development. However, this tool is rarely used in the field of innovation. Purpose. The purpose of this research is to develop of the methodological framework and practice for cooperation mechanisms based on the stimulation of innovation demand and supply in regions of Ukraine. Materials and Methods. The information base of the research is represented by the OECD analytical materials, innovation brokerage platforms of corporations and regions of the world, scholarly research works of leading domestic and foreign researchers, data from the State Statistics Service of Ukraine, which have been studied by the methods of theoretical generalization, analysis and synthesis, systems analysis, economic and statistical analysis. Results. The conceptual framework for the interactions among innovation demanders and suppliers has been proposed; the corresponding mechanisms have been systematized; cooperation among those who supply and those who demand innovation in regions of Ukraine has been assessed; the key characteristics of mechanisms of regional brokerage in the field of innovation and their options for joint territorial communities have been classified, the mechanism of regional brokerage focused on demand-side cooperation has been developed. Conclusions. The mechanisms of regional brokerage contribute to strengthening the innovation capacity of regions by overcoming the fragmentation of regional innovation systems.